Clonal hematopoiesis is associated with adverse outcomes in multiple myeloma patients undergoing transplant - Tarek H. Mouhieddine (Nature Portfolio, 2020)
Multiple myeloma (MM) is treated with induction chemotherapy, autologous stem cell transplant (ASCT) and long-term immunomodulatory drug (IMiD) maintenance. Here, the authors show that the presence of clonal haematopoiesis of indeterminate potential (CHIP) at time of ASCT is associated with adverse outcomes in MM patients.